POLITIK PRAGMATISME DALAM PERSPEKTIF MACHIAVELLISME PADA KEPEMIMPINAN PRESIDEN JOKO WIDODO TAHUN 2014-2024 - Razan Siregar; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
Post-reform political dynamics in Indonesia are characterized by a multiparty system, fluid political coalitions, and intense electoral competition, which necessitate that political leaders adopt adaptive and effective governance strategies. In this context, the leadership of President Joko Widodo during the 2014–2024 period is noteworthy for its tendency toward pragmatic political practices in managing power. This study aims to analyze political pragmatism in Joko Widodo’s leadership through the perspective of Machiavellianism. The research employs a qualitative approach using a literature review method, drawing on secondary data from academic literature, policy documents, institutional reports, and relevant media coverage. The analysis is based on key concepts from Machiavelli’s Il Principe, including power pragmatism, political consolidation, legitimacy management, and the relationship between power and state institutions. The findings indicate that Jokowi’s leadership is characterized by pragmatic political strategies, such as the formation of broad political coalitions, the management of opposition, and the use of public policy and legal instruments to maintain governmental effectiveness and political stability. This study shows that Machiavellian thought remains relevant as an analytical framework for understanding contemporary power practices in Indonesian democracy, particularly in examining leadership that emphasizes strategic flexibility and the sustainability of political stability.